Linguistic Register in Snooker Commentary of the 2023 League Finals - Degaf, Agwin; Sagala, Joelian Aryo Saki; Anggrisia, Nur Fitria (Makassar State University, 2025)
Abstract. Snooker commentary, though often overlooked in linguistic research, presents a rich site for exploring how specialized vocabulary functions in live sporting contexts. In the broader field of sports linguistics, most register studies have concentrated on outdoor sports or E-sports, leaving cue sports like snooker relatively underexplored. This study aims to investigate the linguistic register of snooker commentary by identifying specialized vocabulary and analyzing morphological patterns in two professional finals. Adopting a descriptive qualitative design, data were collected through non-participant observation and note-taking from live broadcasts, comprising 9,146 words of commentary and 525 register-specific terms, which were analyzed using Holmes’ theory of register and McCarthy’s morphological framework with focus on affixation and compounding. The analysis identified 69 unique register terms (e.g., frame-winning visits, potter, baulk color ball), showing that commentators used specialized vocabulary selectively to balance precision and accessibility. Morphological processes such as affixation (potter, doubler) and compounding (long pot, frame-winning visits) were central to constructing efficient, context-sensitive expressions. These findings indicate that register in snooker commentary functions both as a tool for technical description and as a strategy for audience engagement, contributing to broader discussions in sports linguistics and media studies about how specialized registers adapt to diverse audiences in global sporting broadcasts.Keywords: Affixation and Compounding, Morphological Analysis, Register, Snooker Commentary, Sports Linguistics.